2000
DOI: 10.1017/s104795110000915x
|View full text |Cite
|
Sign up to set email alerts
|

Balloon aortic valvotomy through a carotid cutdown in infants with severe aortic stenosis: results of the multi-centric registry

Abstract: This multi-centric registry shows good results in the intermediate term for treating infants with severe aortic valvar stenosis with balloon valvotomy through a carotid arterial cutdown. Infants dependent on prostaglandin had a worse outcome, especially if they had any of the identified risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
1
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 22 publications
1
32
1
4
Order By: Relevance
“…6 A multicenter study assessing outcomes after carotid cutdown in infants found that 12% had abnormalities-ranging from stenosis to complete occlusion-after surgical carotid cutdown and repair, although follow-up imaging was only available in two thirds of patients. 5 The lack of consistent follow-up carotid imaging in most reports of surgical cutdown, therefore, renders direct comparison with carotid patency rates with our PCA cohort difficult. Furthermore, the miniaturization of sheaths and balloon catheters over time could bias older reports of carotid cutdown toward lower carotid patency rates because of the larger sheath sizes that were previously required.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…6 A multicenter study assessing outcomes after carotid cutdown in infants found that 12% had abnormalities-ranging from stenosis to complete occlusion-after surgical carotid cutdown and repair, although follow-up imaging was only available in two thirds of patients. 5 The lack of consistent follow-up carotid imaging in most reports of surgical cutdown, therefore, renders direct comparison with carotid patency rates with our PCA cohort difficult. Furthermore, the miniaturization of sheaths and balloon catheters over time could bias older reports of carotid cutdown toward lower carotid patency rates because of the larger sheath sizes that were previously required.…”
Section: Discussionmentioning
confidence: 96%
“…1 As first described in children by Azzolina et al 2 in 1973, surgical carotid cutdown involved placement of a purse-string suture, followed by creation of a longitudinal arteriotomy through which catheters were placed, and tying of the purse-string suture at the end of the case. Although this approach has been widely used and is considered to be safe and effective, [3][4][5][6] it is invasive, time consuming, requires an available surgeon, and results in scarring that is cosmetically less appealing and could complicate repeat vascular access in the same vessel.…”
mentioning
confidence: 99%
“…Various independent risk factors for valvoplasty outcome identified by the logistic regression have already been reported. In newborns, 21 the risk factors for death were mitral stenosis, short left ventricle, and aortic annulus diameter , 6 mm. In patients 6 weeks to 20 years old, 5 the risk factor for early restenosis was age , 3 years.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the performance of the procedure by our team in a preterm neonate weighing 1.1 kg in 40 minutes resulted in no complications. The multicenter experience shows that the results of aortic valvuloplasty through the carotid route in young infants (< 6 months of age) are very good, with high success indices and low complication rates in patients with no risk factors 20 . Imaging studies show that carotid permeability is maintained in more than 95% of the patients and that neurological complications are exceptional 20 .…”
Section: Discussionmentioning
confidence: 99%